2013
DOI: 10.1371/journal.pone.0054526
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic-Based Model of Radiation-Induced Intercellular Signalling

Abstract: It is now widely accepted that intercellular communication can cause significant variations in cellular responses to genotoxic stress. The radiation-induced bystander effect is a prime example of this effect, where cells shielded from radiation exposure see a significant reduction in survival when cultured with irradiated cells. However, there is a lack of robust, quantitative models of this effect which are widely applicable. In this work, we present a novel mathematical model of radiation-induced intercellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 39 publications
(66 reference statements)
1
71
0
Order By: Relevance
“…Balderson et al 28. investigated heterogeneous doses through a prostate PTV with modeling work that incorporated a bystander effect model derived from in vitro experiments,29 and concluded that a large amount of dose heterogeneity (a standard deviation of 10 Gy about a mean of 78 Gy) through a prostate target volume could be clinically acceptable, and a moderate amount may even be optimal in terms of EUD and TCP. Nielsen et al 30.…”
Section: Discussionmentioning
confidence: 99%
“…Balderson et al 28. investigated heterogeneous doses through a prostate PTV with modeling work that incorporated a bystander effect model derived from in vitro experiments,29 and concluded that a large amount of dose heterogeneity (a standard deviation of 10 Gy about a mean of 78 Gy) through a prostate target volume could be clinically acceptable, and a moderate amount may even be optimal in terms of EUD and TCP. Nielsen et al 30.…”
Section: Discussionmentioning
confidence: 99%
“…Many older models, based on media transfer or co-culture experiments suggested that indirect components are small compared to the direct component, or even mutually exclusive with direct exposures. However, more recent work such as that of Ebert et al, (60) and McMahon et al, (61) suggest that indirect effects may play a significant role not only in out-offield bystander cells, but also on the survival of cells within an irradiated population at high doses, reflecting the significance of intercellular communication in cohort effects, as outlined above. These results may have significant implications for the interpretation of a large portion of radiobiology data as they suggest the traditional paradigm of independent cellular responses may not be valid, with further consequences for the evaluation of many clinical conditions.…”
Section: Predictive Models Of Ribesmentioning
confidence: 97%
“…To fully determine the implications of RIBEs in the clinical context, several attempts to describe predictive frameworks of radiation induced cell signalling have been proposed (53)(54)(55)(56)(57)(58)(59)(60)(61). Generally, these models tend to describe cellular responses to ionising radiation as resulting from two distinct components -a "direct" component, due to radiation interactions within a particular cell, and an "indirect" component resulting from intercellular communication, which is dependent on the exposure across the entire cellular population.…”
Section: Predictive Models Of Ribesmentioning
confidence: 99%
“…Full descriptions of the model and its validation in vitro have been previously published 16,17,25 and are briefly summarized below for completeness.…”
Section: Cell Response Modelmentioning
confidence: 99%
“…13 These observations have been supported by mathematical modelling studies which suggest that intercellular communication may have a significant role in cell death even in populations exposed to doses up to several Gy. [15][16][17][18] Further evidence for these effects has been obtained in small animal models, showing effects of cell signalling in vivo for both tumour 19 and normal tissue response. 20,21 However, whilst these experimental observations demonstrate the effects of intercellular communication in vivo, their role in tumour response following radiotherapy remains to be fully determined.…”
Section: Introductionmentioning
confidence: 96%